ANALISIS MODEL PEMBELAJARAN ACTIVE LEARNING DAN IMPLIKASINYA DALAM PEMBELAJARAN PAK UNTUK PESERTA DIDIK USIA 13-16 TAHUN - Debora Anggreani; Evi Tobeli; Moses Murdiyono (Universitas Kristen Immanuel, 2024)
This research analyzes the Active Learning learning model and its implications in Christian Religious Education (PAK) learning for students aged 13- 16 years. Active Learning is known as an approach that encourages active involvement of students in the learning process, which contrasts with traditional methods which are more passive. This study explores how the application of Active Learning can influence the effectiveness of PAK learning among adolescents. In this context, aspects such as student interaction, active involvement in understanding religious concepts, and their impact on motivation and learning achievement are the main focus. Through this analysis, it is hoped that it can provide in-depth insight into how Active Learning can be optimized in the context of PAK learning to meet the educational needs of students aged 13-16 years.